2015
DOI: 10.1055/s-0035-1550050
|View full text |Cite
|
Sign up to set email alerts
|

Functional Fatigue Alters Lower-extremity Neuromechanics during a Forward-side Jump

Abstract: Neuromuscular fatigue impairs neuromuscular control of the lower extremity. The purpose of the study was to investigate the effect of functional fatiguing exercises on sagittal-plane lower-extremity neuromechanics during a forward-side jump. 21 participants performed 5 forward-side jump tasks before and after functional fatiguing exercises. A functional analysis of variance (FANOVA) evaluated differences between 2 different conditions (pre- vs. post-fatigue) for joint angle, moment, and EMG amplitude during st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
0
17
1
Order By: Relevance
“…Details of the data processing have been described. 30,32 The spatial trajectories of the reflective markers were tracked using Vicon software and exported into Visual 3D (C-Motion, Germantown, MD), and 3D kinematics and kinetics were calculated. Marker trajectories and force-plate data were smoothed using a fourth-order, low-pass Butterworth filter with a cutoff frequency of 6 Hz.…”
Section: Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the data processing have been described. 30,32 The spatial trajectories of the reflective markers were tracked using Vicon software and exported into Visual 3D (C-Motion, Germantown, MD), and 3D kinematics and kinetics were calculated. Marker trajectories and force-plate data were smoothed using a fourth-order, low-pass Butterworth filter with a cutoff frequency of 6 Hz.…”
Section: Data Processingmentioning
confidence: 99%
“…33 Reference muscle-activation data were obtained using a goniometer (model EGM-422; Elite Medical Instruments, Inc, Fullerton, CA) during a 3-second isometric double-legged squat position (458 of knee flexion and 308 of hip flexion) before the walking trials. 32,34 Muscleactivation data were smoothed using a root mean square algorithm with a moving window of 125 milliseconds and normalized to the smoothed reference muscle-activation data using custom-written algorithms in MATLAB (The Math-Works, Inc, Natick, MA). 32,34 The stance phase of walking was defined as the time when the involved foot was in contact with the force plate.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,[7][8][9] Several studies have shown that fatigue can cause a decrease in neuromuscular control and biomechanics during jumping and landing tasks. 3,[10][11][12] Fatigue can be defined as a decline in muscular ability to maintain necessary mechanical work for a given function. 13 Fatigue has also been shown to have many effects on athletic performance, including a decrease in muscle control and strength 13 , decrease in ability to generate power 14 impaired strength, biomechanics, and central activation 12 .…”
Section: Introductionmentioning
confidence: 99%
“…biomechanics, therefore decreasing their abilities to perform a functional test when comparing groups under pre-fatiguing and post-fatiguing conditions. [10][11][12] Limited research has been performed with the TJA in combination with a fatiguing method prior to this current study. [4][5][6][7] The TJA was created to replicate sport activity, however, if fatigue is not achieved, then the validity of the TJA may be limited.…”
Section: Introductionmentioning
confidence: 99%